Register, genre, and style - Biber, Douglas; Conrad, Susan (Cambridge, United Kingdom ; New York, NY : Cambridge Universit y Press, 2019)
"A fully updated and expanded second edition of this flagship work, which introduces methodological techniques to carry out analyses of tex t varieties, and provides descriptions of the most important text varie ties in English. Part I introduces an analytical framework for studying registers, genre conventions, and styles, while Part II provides more detailed corpus-based descriptions of text varieties in English, includ ing spoken interpersonal varieties, general and professional written va rieties and emerging electronic varieties. Part III introduces more adv anced analytical approaches and deals with larger theoretical concerns, such as the relationship between register studies and other sub-discip lines of linguistics, and practical applications of register analysis. A new chapter on EAP and ESP has been added, with new sections on the i mportant differences between academic writing in the humanities and sci ences, and a case study on engineering reports as an ESP register and g enre. Coverage of new electronic registers has been updated, and a new analysis of hybrid registers has been added"--
Machine generated contents note: 1. Registers, genres, and styles: f undamental varieties of language; Part I. Analytical Framework: 2. Desc ribing the situational characteristics of registers and genres; 3. Anal ysing linguistic features and their functions; Part II. Detailed Descri ptions of Registers, Genres, and Styles: 4. Interpersonal spoken regist ers; 5. Written registers, genres, and styles; 6. Academic and professi onal written registers; 7. Registers and genres in interpersonal electr onic communication; 8. Historical evolution of registers, genres, and s tyles; Part III. Larger Theoretical Issues: 9. Multidimensional pattern s of register variation; 10. Register studies in context.
Includes bibliographical references (pages 368-401) and index.
Keywords: Register (Linguistics); Sociolinguistics; English language -- Social aspects